O Podobieństwie Podstawowych Rownań Flü - Borkowski, S. (Engineering Transactions, 1960)
The paper contains a comparison between the basic differential equations of circular cylindrical shells derived by FLÜGGE and VLASOV. As a result of the analysis of these equations it is found that of the nine operators of the FLÜGGE equations seven have a structure identical with that of VLASOV, the difference for the remaining two being very small. It is found also that the operators of the FLÜGGE equations satisfy the fundamental condition (in agreement with the BETTI principle) of the equality of operators located symmetrically in relation to the principal diagonal of the system of equations (2.1).